สมรรถนะของโครงต้านแรงดัดคอนกรีตเสริมเหล็กไร้ความเหนียวภายใต้แผ่นดินไหวรุนแรง - ธนพล ถ้ำแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In the past, there was no legal enforcement on seismic design of buildings in Bangkok area. However, recent seismic data indicates the possibility of having strong earthquakes in surrounding area and the seismic design regulation has been introduced since 2007. That induces the concern about safety of existing buildings under earthquakes. This research studies the vibration and damage characteristics of the buildings under strong earthquakes. The buildings are designed without earthquake loadings to represent the actual conditions of existing buildings. The examples of reinforced concrete buildings having 4- and 10-story are considered including consider the effect of elevation irregularity. The inelastic dynamic analysis is employed using Perform 3D analysis program. The seismic-induced damages are quantified according to ASCE 41-13 standards. About 26 earthquake ground motions are generated assuming their epicenters are along the Three Pagodas fault in Kanchanaburi. The effects of brick walls, stiffness degradation and strength deterioration of the building are not included. The obtained results indicate the seismic damage characteristics of the example buildings. Then the damage scenario of existing buildings in the city under strong earthquakes is discussed.